"Analysis of pesticide residues in fruits and vegetables using gas chromatography-high resolution time-of-flight mass spectrometry". Issue 5 (5th February 2015) - Valles, Noelia Belmonte; Uclés, Samanta; Besil, Natalia; Mezcua, Milagros; Fernández-Alba, Amadeo R.
Abstract : This work reports a study on the operational parameters and development of a rapid automatic method for determining pesticide residues in fruit and vegetables using gas chromatography-high resolution time-of-flight mass spectrometry. Abstract : This work reports a study on the operational parameters and development of a rapid automatic method for determining pesticide residues in fruit and vegetables using gas chromatography full spectra mass acquisition time-of-flight accurate mass spectrometry (GC-TOF-MS) in electron ionization mode (EI) based on the use of an "in-house" accurate-mass database. The database contains 110 GC amenable compounds, with their main fragment ions obtained under electron ionization at 70 eV. In addition, it includes the retention times of each pesticide working at constant flow. This customized database was linked to commercial software, which extracted all the potential compounds of interest from the GC-TOF MS raw data for each sample and matched them against the database to search for the targeted compounds in the sample. Ethyl acetate extracts spiked at 10, 20, 50 and 100 μg kg −1 levels in tomato, orange and spring onion were tested using the automatic detection of the target pesticides; at 10 μg kg −1, 100% of pesticides in tomato, 97.8% of pesticides in spring onion and 95.6% in orange were detected. These results were obtained under an acquisition rate of 4 GHz (12 000 FWHM) and a mass error tolerance of 5 ppm. The retention time window for detection and identification was ±0.2 min. Adequate linear responses in the 10–100 μg kg −1 range were obtained for all the compounds in all the matrices, although saturation effects were observed in some cases. The developed method was applied to real samples with the qualitative and quantitative results comparable to those obtained using GC-QqQ-MS/MS.